2006
DOI: 10.1016/j.tet.2006.01.084
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dimethyl-2-(3-nitro-1,2,4-triazol-1-yl)-2-pyrrolidin-1-yl-1,3,2-diazaphospholidinium hexafluorophosphate (MNTP): a powerful condensing reagent for phosphate and phosphonate esters

Abstract: A novel phosphonium-type condensing reagent,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The progression of the reaction was followed by 31 P NMR spectroscopy either by performing the H-phosphonate coupling in the NMR tube (CD 3 CN) or by NMR spectroscopic analysis of a small aliquot of the reaction mixture. The reaction is supposed to proceed through formation of the reactive tetracoordinated P III -intermediates such as H-pyrophosphonates[ 49 ] and nitrotriazol-1-yl-phosphites,[ 50 ] which can be detected by 31 P NMR spectroscopy in the absence of hydroxylic component. Upon shortage of nucleophilic component 27 , activation of Ara4N H-phosphonate 6 resulted in eventual formation of nitrotriazol-1-yl-H-phosphonate 6 a (Supporting Information, Figure 2 ), which was detected by 31 P NMR spectroscopy ( δ =13.1 and 14.1 ppm, J PH =652 and 656 Hz, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The progression of the reaction was followed by 31 P NMR spectroscopy either by performing the H-phosphonate coupling in the NMR tube (CD 3 CN) or by NMR spectroscopic analysis of a small aliquot of the reaction mixture. The reaction is supposed to proceed through formation of the reactive tetracoordinated P III -intermediates such as H-pyrophosphonates[ 49 ] and nitrotriazol-1-yl-phosphites,[ 50 ] which can be detected by 31 P NMR spectroscopy in the absence of hydroxylic component. Upon shortage of nucleophilic component 27 , activation of Ara4N H-phosphonate 6 resulted in eventual formation of nitrotriazol-1-yl-H-phosphonate 6 a (Supporting Information, Figure 2 ), which was detected by 31 P NMR spectroscopy ( δ =13.1 and 14.1 ppm, J PH =652 and 656 Hz, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Coupling of H ‐phosphonate 5 was performed with chlorotripyrrolidinophosphonium hexafluorophosphate (PyTP) followed by conversion into the silylated phosphite triester with bis(trimethylsilyl)acetamide (BSA) and subsequent oxidation with camphorsulfonic acid (CSO) . This approach, however, produced the diester derivative 19 only in a poor yield.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the subsequent key P V coupling reaction of 30 with 34 under the agency of TMBSC and MNO afforded a mixture of the fully protected target compound me‐ADPR ( 32 ) and its monodemethylated analogue in a combined yield of 60 %. Previously, Wada and co‐workers had shown that phosphonium reagents are selective activators and effective agents for the condensation of methylphosphonates with alcohols . Using 3‐nitro‐1,2,4‐triazol‐1‐yl‐tris(pyrrolidin‐1‐yl)phosphonium hexafluorophosphate (PyNTP) as the condensation agent further improved the yield of protected me‐ADPR ( 32 ) to 84 % (Figure S5).…”
Section: Figurementioning
confidence: 99%